The Concept of Tabarruj in the Qur’an according to Muslim Commentators - Mirna Wati; Hasep Saputra (Institut Agama Islam Negeri (IAIN) Curup, 2018)
Today there are still many Muslimah dressed not in accordance with the rules in the Islamic religion. Good dress habits must be planted early so that the Muslimah get used to and make Islamic dress codes entrenched in society. Tabarruj is a woman's style of dress or attitude that is excessive in order to attract the attention of others when she comes out of her house, deliberately showing the beauty of her face and body and waving her way so that she can see the jewelry in front of other people. the Aim of this research is to know the understanding of paragraph about tabarruj in the Qur'an, inside about rule dressed up or be decorated for woman. In this study the researcher used library research with the method of maudhu'i of interpretation which collects verses of the Quran based on the topic or theme set by all the verses collected based on the period of decline, then studied in depth and thoroughly from various aspects that can be explored, then pay attention to these verses with explanations and relationships with other verses. The Results show that tabarruj in the Qur'an is style dressed up or attitudes woman on purpose interesting other people's attention when she go out from her house and show her beauty.